2009
DOI: 10.1111/j.1365-294x.2009.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible social organization and high incidence of drifting in the sweat bee, Halictus scabiosae

Abstract: The very diverse social systems of sweat bees make them interesting models to study social evolution. Here we focus on the dispersal behaviour and social organization of Halictus scabiosae, a common yet poorly known species of Europe. By combining field observations and genetic data, we show that females have multiple reproductive strategies, which generates a large diversity in the social structure of nests. A detailed microsatellite analysis of 60 nests revealed that 55% of the nests contained the offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…Direct reproduction by unrelated intruders has been reported in several bee species 19,33,34 . In our data, the intruders take their own share of direct reproduction; however, the members of the host nests obtained similar level fitness comparing with the eusocial nests without intruders (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct reproduction by unrelated intruders has been reported in several bee species 19,33,34 . In our data, the intruders take their own share of direct reproduction; however, the members of the host nests obtained similar level fitness comparing with the eusocial nests without intruders (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, worker behaviour in L. baleicum would be beneficial to the queens and workers. The F0 females of halictid bees maintain their nests without helpers during the first reproductive period 12,13,16,19 . It has been suggested that the lack of lifetime monogamy may prevent the halictid bees from lifetime eusociality 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent behavioral studies may shed some light on this observation. Although this species is eusocial, individuals also show a large degree of drifting among nests, and females will often leave their natal nests to reproduce in nests of unrelated individuals (56,57). Many halictids mark nests with chemical cues, and these odors are used by guards to distinguish nestmates and nonnestmates (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…In this species, foundresses rear a first brood consisting principally of relatively small females that help their mother to rear a second brood of males and gynes (Brand and Chapuisat 2012). The first-brood females have the possibility to mate and reproduce, either in their natal nests or in other nests (Ulrich et al 2009). Hence, it is interesting to examine whether helpers really increase colony survival and productivity, and by how much.…”
Section: Introductionmentioning
confidence: 99%